ИБРАТНИНГ ЖАМИЯТШУНОСЛИККА ҚЎШГАН ҲИССАСИ (Scientific journal of the Fergana State University, 2023)
This article is about  Ishakhan Ibrat’s contribution to the social science through analysis and interpretation his work “Mezon uz-zamon”. The author “Mezon uz-zamon” paid attention that one of the nine of the criteria which includes the balance of time. Not only tried he gives abundant information and reacted to them as but as well.